BTN Syariah Bank's Strategy in Resolving Problematic Mortgage Financing (Case Study at BTN Syariah Bank's Indramayu Branch Office) - Muhamad As'ad (Kawakib: Journal of Multidisciplinary Research, 2025)
Along with the rapid development of the sharia banking sector in Indonesia, Bank BTN Syariah, as one of the banking institutions that prioritizes sharia principles, is facing various challenges in resolving problematic KPR (Home Ownership Credit) financing. This problem arises in line with the increasing number of customers who are unable to fulfill their installment payment obligations due to various factors, such as unstable economic conditions, unemployment, or a decline in people's purchasing power. Apart from that, limited understanding of sharia banking products also exacerbates this problem. Effective resolution of problematic mortgage financing is crucial to maintaining the sustainability of bank operations, while ensuring that the settlement process remains in accordance with sharia provisions. Therefore, it is important for Bank BTN Syariah to implement a strategy that not only prioritizes financial aspects, but also considers humanitarian and sharia aspects, with the aim of helping customers get out of financial difficulties without violating the principles established in sharia banking. Success in resolving problematic financing will determine the bank's reputation in the eyes of the public and customers, as well as contribute to the stability of the sharia banking sector in Indonesia.